Perilaku Gender dan Kontribusinya Terhadap Kebersihan Lingkungan di Kota Pekalongan - Hermawan, Raji (IAIN Pekalongan, 2019)
This article aims to find a description of gender behavior and its contribution in maintaining cleanliness in the city of Pekalongan, with a sample of 100 respondents each of 50 men and 50 women, selected randomly in several areas in the city of Pekalongan. This type of research is a qualitative descriptive study with a survey method. Data retrieved using a questionnaire, observation, and documentation. The results showed that men's behavior was more able to maintain environmental hygiene than women, as evidenced from the group of men 62% had behaviors that care about environmental hygiene, while from the group of women, only 46% had behaviors that care about environmental hygiene. There is a need for awareness of environmental hygiene through various approaches, both religious and social so that the people of Pekalongan city take responsibility for environmental hygiene. Islam encourages people to always maintain the cleanliness of the environment, cleanliness is part of faith. Humans both men and women have the same obligation in maintaining environmental hygiene. As khalifah fil ardh, human obligation is not limited to worshiping Allah SWT only. He also has an obligation to maintain the preservation of the natural environment with discipline in disposing of waste. The reality on the ground, there are still many people who do not maintain environmental hygiene by not disciplining waste disposal, especially in the city of Pekalongan.